Culture, trust and business ecosystems: the mediating role of online chat in China. (2018) - Rong, Ke; Secchi, Davide; Shou, Yongyi
This paper analyses the case of Taobao (the B2C and C2C platform of Alibaba Group), the 'focal firm' in a large online shopping ecosystem in China. The study attempts to reframe the business ecosystem considering the impact of cultural dimensions. Findings show that in a society with strong culture of guanxi and collectivism, a computer-mediated online communication tool works as a surrogate for real-life experience of socially binding behaviours to organise ecosystem stakeholders such as online marketplace owners, customers and sellers. The perception of collectivism affects the effectiveness of the communication tool, which, in turn, facilitates trust building between sellers and buyers. The result is unique and tied to a society dominated by guanxi and collectivism, and shows how it addresses socio-cultural needs through a computer-mediated communication technology.